2005
DOI: 10.1136/gut.2004.049403
|View full text |Cite
|
Sign up to set email alerts
|

Anti-monocyte chemoattractant protein 1 gene therapy attenuates experimental chronic pancreatitis induced by dibutyltin dichloride in rats

Abstract: Background: Monocyte chemoattractant protein 1 (MCP-1) is a member of the C-C chemokine family and exerts strong chemoattractant activity in monocytes, macrophages, and lymphocytes. Rat pancreatic fibrosis induced by dibutyltin dichloride (DBTC) is considered to be an appropriate chronic pancreatitis model histologically and enzymatically, as has demonstrated in a previous study. Aim: We examined the effect of human dominant negative inhibitor of MCP-1 (mutant MCP-1) on progression of chronic pancreatitis indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…[51][52][53] As a result of increased recruitment of inflammatory cells, activated mononuclear cells release profibrotic cytokines and chemokines, such as TGF-b, TNF-a and MCP-1, which in turn activate hPSCs and promote fibrosis in CP. 4,52,53 The chemokine MCP-1, one of the major monocyte chemoattractants, is highly expressed in fibroblasts in CP, induces TGF-b upregulation and is associated with the progression of pancreatic fibrosis. 52,54 Blocking of MCP-1 attenuates the degree of fibrosis in experimental CP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[51][52][53] As a result of increased recruitment of inflammatory cells, activated mononuclear cells release profibrotic cytokines and chemokines, such as TGF-b, TNF-a and MCP-1, which in turn activate hPSCs and promote fibrosis in CP. 4,52,53 The chemokine MCP-1, one of the major monocyte chemoattractants, is highly expressed in fibroblasts in CP, induces TGF-b upregulation and is associated with the progression of pancreatic fibrosis. 52,54 Blocking of MCP-1 attenuates the degree of fibrosis in experimental CP.…”
Section: Discussionmentioning
confidence: 99%
“…52,54 Blocking of MCP-1 attenuates the degree of fibrosis in experimental CP. 52 Regarding fractalkine and fibrosis, CX3CR1 was identified to have a genetic and functional importance in higher stages of liver fibrosis in chronic hepatitis C, and was noticeably upregulated in patients with enhanced renal fibrosis. 21,22 In experimental post-ischemic renal fibrosis, fractalkine and CX3CR1 expression levels were associated with enhanced inflammation and fibrosis, which could be diminished by blocking antibodies to CX3CR1 through the reduction of a-SMA and Collagen-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental model of chronic pancreatitis was induced by a single intravenous administration of dibutyltin dichloride (DBTC), as described elsewhere. 31 Briefly, DBTC (SigmaAldrich, China) was first dissolved in 100% ethanol (two parts) and mixed with glycerol (three parts), then the DBTC solution was injected into the tail vein at a dose of 8 mg∕kg body weight.…”
Section: Animal Model and Preparation Of Specimensmentioning
confidence: 99%
“…13 Recent studies have also reported that chemokines other than MCP-1 induce inflammation and fibrosis in other organs, and that multiple chemokines are involved in chronic inflammation.…”
mentioning
confidence: 99%